Using Geogebra and Manipulative’s on Conics as Learning Tool for Student - Eyus Sudihartinih; Tia Purniati; Ade Rohayati (EduMa: Mathematics education learning and teaching, 2020)
Students are required to complete tasks related to eccentricity in the conic. If the eccentricity is changed the value is obtained through different forms of conic. If the eccentricity is equal to zero, then in order to form a special ellipse conic that is a circle. To assist students in learning it required the learning media such as manipulatives and Geogebra software. The participants of this study were second-semester students who studied analytical geometry in the department of mathematics education at one of the universities in Indonesia. The number of participants were 32 students consisting of 10 men and 22 women. We find that students generally accomplish tasks very well. Students complete the task well by using learning media. Therefore, manipulative and geogebra can be used as an alternative to learning mathematics